Successful Deep Inferior Epigastric Perforator Flap Harvest despite Preoperative Therapeutic Subcutaneous Heparin Administration into the Abdominal Pannus - Joseph W. Duncumb; Kana Miyagi; Parto Forouhi; Charles M. Malata (Case Reports in Surgery)
Abdominal free flaps for microsurgical breast reconstruction are most commonly harvested based on the deep inferior epigastric vessels that supply skin and fat via perforators through the rectus muscle and sheath. Intact perforator anatomy and connections are vital for subsequent optimal flap perfusion and avoidance of necrosis, be it partial or total. The intraflap vessels are delicate and easily damaged and it is generally advised that patients should avoid heparin injection into the abdominal pannus preoperatively as this may compromise the vascular perforators through direct needle laceration, pressure from bruising, haematoma formation, or perforator thrombosis secondary to external compression. We report three cases of successful deep inferior epigastric perforator (DIEP) flap harvest despite patients injecting therapeutic doses of low molecular weight heparin into their abdomens for thrombosed central venous lines (portacaths™) used for administering primary chemotherapy in breast cancer.